Quality of life of the elderly in a rural community in the State of Mexico - Villalobos Monroy, Guadalupe; Franco Alejandré, Diana; Gaspar del Angel, Blanca Lilia (Con texto humano; Vol 2 No 1 (2023): enero - junioDO - 10.36677/contextohumano.v2i1.20451, 2023)
The objective of this article is to understand the reasons and consequences of population aging and their quality of life, focusing on a rural community in the State of Mexico. It is a descriptive study; the sample consisted of 104 older adults in a rural community of San Antonio la Isla, State of Mexico. The WHO World Health Organization Quality of Life-Old instrument was applied. Results. Regarding the sociodemographic profile, 59.61% of the MAs did not have basic education. 12.5% of the MA presented chronic degenerative diseases. A total of 28.84% indicated that the impairment of one or more of their senses had a significant impact on their daily life.